Placenta accreta and uterine rupture of unscarred uterus in patients with systemic lupus erythematosus with prolonged steroid exposure: a report of two cases - H.M. Kim; Y.J. Chin; H.H. Cha; W.J. Seong; M.J. Kim (IMR Press, 2020)
We experienced two cases of placental abnormalities or uterine rupture in patients with systemic lupus erythematosus (SLE), necessitating cesarean hysterectomy and leading to massive hemorrhage that required large transfusions. So we introduced the possibility of abnormal placentation and uterine rupture as well as preeclampsia, preterm labor, and fetal growth restriction needs to be considered in pregnant women with SLE who have been taking steroids, even if low dose, for prolonged periods and who do not have any other risk factors.